2018
DOI: 10.1186/s12870-018-1470-7
|View full text |Cite
|
Sign up to set email alerts
|

Two virulent sRNAs identified by genomic sequencing target the type III secretion system in rice bacterial blight pathogen

Abstract: BackgroundSmall non-coding RNA (sRNA) short sequences regulate various biological processes in all organisms, including bacteria that are animal or plant pathogens. Virulent or pathogenicity-associated sRNAs have been increasingly elucidated in animal pathogens but little is known about similar category of sRNAs in plant-pathogenic bacteria. This is particularly true regarding rice bacterial blight pathogen Xanthomonas oryzae pathovar oryzae (Xoo) as studies on the virulent role of Xoo sRNAs is very limited at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Work in the last decade has identified three virulence-related sRNAs amongst a number of other sRNAs in different Xanthomonas species (Jiang et al, 2010;Liang et al, 2011;Schmidtke et al, 2012Schmidtke et al, , 2013Hu et al, 2018). Nevertheless, the inventory of sRNAs in Xanthomonas is probably far from complete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work in the last decade has identified three virulence-related sRNAs amongst a number of other sRNAs in different Xanthomonas species (Jiang et al, 2010;Liang et al, 2011;Schmidtke et al, 2012Schmidtke et al, , 2013Hu et al, 2018). Nevertheless, the inventory of sRNAs in Xanthomonas is probably far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…campestris (Xcc) is the causal agent of black rot disease of cruciferous crops (Mansfield et al ., 2012; Vicente and Holub, 2013) and is a member of a genus of phytopathogenic bacteria that infect many economically important crops causing severe disease and economic losses (Ryan et al ., 2011; An et al ., 2019). Work in the last decade has identified three virulence‐related sRNAs amongst a number of other sRNAs in different Xanthomonas species (Jiang et al ., 2010; Liang et al ., 2011; Schmidtke et al ., 2012, 2013; Hu et al ., 2018). Nevertheless, the inventory of sRNAs in Xanthomonas is probably far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…The Hfq chaperone mediates interactions between sRNAs and their targets helping to improve base-pair recognition (Massé et al, 2003;Lenz et al, 2004;Holmqvist and Vogel, 2018;Santiago-Frangos et al, 2019). This protein binds to the regulatory RNAs, helps to stabilize them, and leads the base pairing with the targets (Hu et al, 2018;Han et al, 2019). Hoekzema et al (2019) have suggested an additional mechanism, where the action of Hfq will unfold a hairpin in the targeted mRNA.…”
Section: Prokaryotic Srnasmentioning
confidence: 99%
“…oryzae ( Xoo ), which is closely related to Xoc , a recent study identified sRNAs trans217 and trans3287 as virulence-associated sRNAs that are required for pathogenicity in susceptible rice plants and for the elicitation of the hypersensitive response in nonhost plants. The authors suggested that these sRNAs directly regulate the T3SS in Xoo [ 18 ]. In a prior study [ 19 ], eight sRNAs were functionally characterized in Xoo ; among these, sRNA-Xoo1 was of special interest because it was conserved in other Xanthomonas spp., and its expression was Hfq-dependent.…”
Section: Introductionmentioning
confidence: 99%